2011
DOI: 10.1523/jneurosci.5489-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Is the Medial Posterior Parietal Area V6A a Single Functional Area?

Abstract: The visuomotor medial posterior parietal area V6A has been recently subdivided into two cytoarchitectonic sectors called V6Ad and V6Av (Luppino et al., 2005). The aim of the present study was to recognize whether these two cortical sectors show different functional profiles. Fourteen hemispheres from eight animals (Macaca fascicularis) were included in this study, for a total of 3828 extracellularly recorded neurons assigned to areas V6Ad or V6Av on cytoarchitectural basis. The sensitivity of recorded neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
139
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 41 publications
12
139
0
Order By: Relevance
“…Since ϳ60% of V6A neurons are responsive to visual stimulation (Galletti et al, 1996;Gamberini et al, 2011), it could be that the precocious fixation-related discharges we observed are actually visual responses to the fixation-LED appearance. To check this possibility, we compared in single cells the activity during FIX in the preferred position with that recorded when the monkey was sporadically fixating at that same location at the beginning of the trial, before LED onset (Student's t test, p Ͻ 0.05).…”
Section: Time Course Of Fixation-related Activitymentioning
confidence: 92%
See 2 more Smart Citations
“…Since ϳ60% of V6A neurons are responsive to visual stimulation (Galletti et al, 1996;Gamberini et al, 2011), it could be that the precocious fixation-related discharges we observed are actually visual responses to the fixation-LED appearance. To check this possibility, we compared in single cells the activity during FIX in the preferred position with that recorded when the monkey was sporadically fixating at that same location at the beginning of the trial, before LED onset (Student's t test, p Ͻ 0.05).…”
Section: Time Course Of Fixation-related Activitymentioning
confidence: 92%
“…The anatomical reconstruction of recording sites was performed using the cytoarchitectonic criteria described by Luppino et al (2005) and the functional criteria detailed by Galletti et al (1999a) and Gamberini et al (2011). Figure 3A is a posterolateral view of the partially dissected macaque brain that shows the location of area V6A.…”
Section: Recording Sitementioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, one section of every five was stained with the Nissl method (thionin, 0.1% in 0.1 M acetate buffer, pH 3.7) for the cytoarchitectonic analysis. Procedures to reconstruct microelectrode penetrations and to assign neurons recorded in the anterior bank of the parieto-occipital sulcus to area V6A were as those previously described by our group (Galletti et al, 1996(Galletti et al, , 1999a(Galletti et al, , 1999bGamberini et al, 2011). Briefly, electrode tracks and the approximate location of each recording site were reconstructed on histological sections of the brain on the basis of the lesions and several other cues, such as the coordinates of penetrations within the recording chamber, the kind of cortical areas passed through before reaching the region of interest, and the depths of passage points between gray and white matter.…”
Section: Histological Reconstruction Of Electrode Penetrationsmentioning
confidence: 99%
“…It has been reported that area V6A contains visual neurons that are very sensitive to the orientation of visual stimuli (Galletti et al, 1996(Galletti et al, , 1999aGamberini et al, 2011), thus providing critical information for object grasping .…”
Section: Introductionmentioning
confidence: 99%